Historical trajectories and lost heritage of early Chinese schools in Singapore – case study of Yeung Ching School in ‘Chinatown’ - Qu, Jingyi (2020)
The history of modern Chinese schools in Singapore may be traced back to the early 20th century, when efforts to provide vernacular education in the British colony were made by community leaders across Chinese dialect groups, with support of the Qing Empire. Only a handful of these were selected as elite schools for bilingual education under the Special Assistance Plan (SAP) introduced in 1979 in independent Singapore. This paper examines the historical trajectories of these early schools from early association with Chinese nationalism to becoming multi-ethnic schools or simply defunct. It will focus on the case of the former Yeung Ching School in ‘Chinatown’ catering to the Cantonese community, to explore how the legacy of a Chinese school may be impacted by state formation and urban development since the 1950s, and also to point out a gap in current heritagisation pertaining to the role of education in shaping cultural identities.